Pedagogical conditions for the development of cognitive independence in physical education lessons - Kairgozhin, Dulat; Kuzembayeva, Gulzhana; Maydangalieva, Zhumagul; Bakhtiyarova, Sayagul; Mugauina, Gulbaram (Journal of Education and e-Learning Research, 2023)
Cognitive Independence (CI), which physical education has a high potential for fostering in students, is characterized by a developed set of cognitive skills, an ideal level of knowledge, a strong value attitude towards cognition, and competencies related to the ability and willingness to take the initiative and engage in professionally responsible activities. However, the biggest challenges for physical education teachers stem from a lack of program material that clearly defines the content of lessons for the development of students’ CI as well as the stages of their entrance into the educational process. The purpose of the study is to theoretically justify and methodologically support the process of developing students’ CI in physical education lessons. The methodology used in the study comprises a quasi-experimental pretest-posttest research design. The study participants included 210 students in grades 10 and 11 from two secondary schools in the city of Atyrau (the Republic of Kazakhstan) and teachers acting as experts. The study findings revealed substantial variations in the dynamics of students’ CI in the control and experimental groups, confirming the efficiency of the application of the built-in model and technology. Despite the limitations, which lie in the fact that not all aspects of the development of students’ CI in physical education lessons were considered, this study has provided the theoretical justification and methodological support for development of students CI in physical education lessons that might contribute to efficient specialists’ training.